A meerkat diary : my journey into the wild world of a meerkat mob - Eszterhas, Suzi (Owlkids Books, 2024)
"Join the author of Moto and Me and My Leopard Diary as she spends two wild and action-packed weeks observing and photographing a mob of meerkats. Suzi's diary opens with her arrival on the Kalahari Desert in Botswana, where she and her zoologist assistant, Becky, are welcomed by Motto, a local meerkat habituator, and Villa, a naturalist guide. Over the next action-packed two weeks, Suzi and the team observe a small but mightily busy meerkat mob. Her daily accounts describe the early life of the five meerkat pups being raised by the mob's matriarch and two adult males. The pups grow from tiny creatures who wobble as they walk and are wholly dependent on their adult caretakers, to adolescents who practice killing scorpions for their dinner and have nearly perfected the famous tripod stance meerkats use when on the lookout for danger. Along the way, the mob survives a heavy rainfall that floods the plains where they live, as well as manage to avoid becoming the dinner of a hungry eagle hunting them from overhead. They even escape being trampled by a galloping herd of zebras -- which Suzi and Becky also just escape thanks to Motto and Villa's quick thinking. In addition to her observations about the mob, Suzi's narration seamlessly weaves in information about life in the heart of the Kalahari Desert -- from the other wild animals that are native to the area (including a brown hyena mother and cub, an eagle, jackals, a porcupine, and lions) to an afternoon spent with some of the indigenous Ju/'hoasi people who have thrived there for tens of thousands of years. Endmatter includes a Q&A with both Motto and Villa, who play such essential roles in this adventure. Jam-packed with amazing and often adorable photos."--